Financial Crime: An Evaluation into Current Risks, Detection Methods and Regulation - Whitehead, Sarah I. (2020)
This thesis examines financial crime in the global banking markets with specific focus on its risks, how institutions detect illegal activity and evaluates the associated regulatory environment. The study utilises empirical feedback from a number of industry experts to reinforce the findings of the extensive literature review.